2014
DOI: 10.1080/09168451.2014.882742
|View full text |Cite
|
Sign up to set email alerts
|

Potential of extracts from Saponaria officinalis and Calendula officinalis to modulate in vitro rumen fermentation with respect to their content in saponins

Abstract: Saponins have the potential to favorably modulate rumen fermentation, but there is generally a lack of the chemical structures associated with the described effects. The activity of extracts from Calendula officinalis and Saponaria officinalis in the rumen was evaluated in vitro. The S. officinalis root extract, reduced CH4 production by 8.5% and increased total VFA concentration by 25.2%. C. officinalis and S. officinalis root extracts and the S. officinalis aerial part extract decreased the acetate to propio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
(25 reference statements)
1
15
0
2
Order By: Relevance
“…These extracts have been known to contain a relatively high percentage of saponins, which have been used in medicine and cosmetics (Budan et al 2014). According to Budan et al (2014), the content of saponins in S. officinalis roots can range between 224.0 and 693.8 mg/g of dry matter. The soapwort extract itself contains 11.6-19.6% total saponin, which increases the importance of soapwort (Battal 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These extracts have been known to contain a relatively high percentage of saponins, which have been used in medicine and cosmetics (Budan et al 2014). According to Budan et al (2014), the content of saponins in S. officinalis roots can range between 224.0 and 693.8 mg/g of dry matter. The soapwort extract itself contains 11.6-19.6% total saponin, which increases the importance of soapwort (Battal 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly known that the major effect of saponins on rumen fermentation is an increased production of propionate and decreased acetate to propionate ratio (Wina et al 2005). Moreover, Budan et al (2014) recently observed in an in vitro experiment that S. officinalis root extract increased total VFA concentration in the rumen and markedly decreased acetate to propionate ratio. In an earlier experiment, Cieslak et al (2014) obtained similar results using S. officinalis root powder in in vitro ruminal fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…Most applications of soapwort rely on its high content of surface‐active saponins, reaching 1.7–8.6% in the rhizomes (Budan et al, , ; Lu et al, ; Sadowska et al, ; Szczechowiak et al, ). Saponins belong to secondary metabolites, whose biological role is still not clear, although several reports point to their possible activity in defense against predators and pathogens (Osbourn et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent work of Bellenot et al () provides some hints on how different saponin profiles can be in the underground and aerial parts of soapwort. Nevertheless, still very little is known about the variability of saponin content in different plant organs and at different stages of the plant development.…”
Section: Introductionmentioning
confidence: 99%